Investigation of preferred leadership behaviors in sport and empathic tendency with regards to different variables - Gaye Erkmen; Mehibe Akandere (Türk Spor ve Egzersiz Dergisi)
This study was conducted in order to explore the emphatic tendencies of students receiving education at the School of Physical Education and Sport as well as the leadership behaviors they prefer with regard to different variables. The sampling of the study involved a total of 361 students with 138 female and 223 male students. Empathic tendencies Scale (ESS) preferred leadership behavior form of Leadership for Sport Scale were used for data collection. In the analysis of data, depending on the variables, independent samples t-test, one-way variance analysis and Pearson product-moment correlation coefficient method was utilized. In order to determine the source of differentiation in findings which were significant differences as ANOVA was conducted. In consequence of the analyses, whereas no difference was found among empathic tendency scores with regard to gender variable, significant difference was found in sub-dimensions of preferred leadership behaviors; social support, democratic behavior, autocrative behavior. With regard to sport type variable, among the empathic tendency scores a statistically significant difference was observed in democratic behavior sub-dimension. As a result of the analysis carried out in an effort to determine the correlation between empathic tendency and preferred leadership behavior, positive and significant relationships were observed between social support, positive feedback and training and instruction sub-dimensions and empathic tendencies. Findings indicated that individuals who were captain have higher empathic tendency scores than those who were not.